Solar Ultraviolet Radiation for Psoriasis Treatment at Nakhon Pathom Province - Buntoung, Sumaman; Pattarapanitchai, Somjet; Laiwarin, Pradthana; Boontaveeyuwat, Einapak; Janjai, Serm (Journal of Applied Research on Science and Technology (JARST), 2022)
Psoriasis is one of the long-term (chronic) skin diseases that cause problems to the immune system. Artificial light source in ultraviolet radiation (UV) wavelength, especially in the UV-B band, is one of the standard treatments for psoriasis. Alternatively, natural sunlight is also used for the treatment, called heliotherapy. Consistent solar radiation at a particular location and time is key to successfully giving a safe and effective natural sunlight treatment. Therefore, in this study, solar ultraviolet radiation for psoriasis heliotherapy at a site in Thailand was first investigated to reveal its diurnal and seasonal variations and efficiency in the therapy. A spectroradiometer (DMc150) installed at Silpakorn University, Nakhon Pathom province (13.82 ºN, 100.04 ºE) was used to measure spectral irradiance and converted to anti-psoriasis irradiance. This irradiance was calculated to obtain the monthly average hourly anti-psoriasis ultraviolet radiation data (2016-2018). The result showed the diurnal and seasonal variations of the anti-psoriasis ultraviolet radiation. The values are relatively high from 10 a.m. to 2 p.m., especially between March and October, and relatively low from November to February. The maximum monthly average hourly values in the summer, rainy, and winter seasons were 77.6, 76.9, and 52.4 mJ/cm2. In addition, an empirical model for estimating the anti-psoriasis ultraviolet radiation dose was first generated as a linear regression by using the UV index, which is a broader measurement. The difference between the data obtained from the model and the measurement is in good agreement with root mean square difference (RMSD) and mean bias difference (MBD) were 12.9% and 1.0%, respectively.